Class I and II Histone Deacetylase Inhibitor LBH589 Promotes Endocrine Differentiation in Bone Marrow Derived Human Mesenchymal Stem Cells and Suppresses Uncontrolled Proliferation - Schröder, Christoph; Khatri, Rahul; Petry, Sebastian Friedrich; Linn, Thomas (Experimental and Clinical Endocrinology & Diabetes, 2020)
Mesenchymal stem cells are useful tools employed in clinical and preclinical medicine. Their beneficial potential in especially degenerative as well as autoimmune diseases is a constant focus of research. Regarding diabetes mellitus, transplantation of stem cells is seen as a possible therapeutic approach to overcome the loss of endocrine pancreatic cells. It was reported that co-transplantation of mesenchymal stem cells with pancreatic islet cells improves function and survival of the graft. However, these multipotent progenitors may be able to form tumors, especially under immunosuppressed conditions. Histone deacetylase inhibitors might offer the potential to overcome this issue. These small molecules can induce cell differentiation and control proliferation. Their potential to control lineage development of stem cells has been distinctly demonstrated in the treatment of cancer, mainly in hematopoietic neoplasias.In this study, we demonstrate that human bone marrow-derived mesenchymal stem cells exhibit low carcinogenic potential in an immunosuppressed condition in vivo. Further, the effect of histone deacetylase inhibitors LBH589, MS-275, and MGCD0103 was examined after normalizing histone deacetylase activities in culture. Interestingly, transcripts of insulin gene enhancer protein and paired-box-gene 6, two markers of pancreatic endocrine differentiation were constitutively expressed in the cell line. The broad spectrum inhibitor of class I and class II histone deacetylases LBH589 upregulated the expression of these transcription factors in a significant way, whereas addition of selective class I histone deacetylase inhibitors MS-275 and MGCD0103 did not result in significant changes in gene expression.In conclusion, we deliver evidence that a combined class I and II histone deacetylase inhibition is able to modulate the transcripts of differentiation markers of mesenchymal stem cells. The treatment holds the capability to facilitate endocrine differentiation in future approaches to replace endocrine cells by stem cell therapy.
Keywords: HDAC; Isl1; Pax6; islet transplantation; tumor formation